Estrogen can abolish oxytocin-induced spinal anti-hyperalgesia. (February 2022) - Chow, Lok-Hi; Wu, Wan-Chuan; Kuo, Chun-Lin; Hung, Hao-Yuan; Chen, Yuan-Hao; Pan, Weihong; Huang, Eagle Yi-Kung
Abstract: Our previous study verified a sex difference of anti-hyperalgesia in rats and anti-allodynia in mice induced by intrathecal oxytocin (OT). In the model of intraplantar carrageenan-induced inflammatory hyperalgesia, intrathecal OT injection induced a substantial anti-hyperalgesia in male rats even at a low dose (0.125 nmol). In contrast, female rats only responded to an extremely high dose (1.25 nmol). This sex difference concurs with a lower expression of OT receptors and higher expression of insulin-regulated aminopeptidase (IRAP; OT degrading enzyme) in the spinal cords of female rats. In this study, we further determined the role of female hormones in this sex difference by using ovariectomized rats. Our results show that a low dose of intrathecal OT caused a significant anti-hyperalgesia effect in ovariectomized female rats, similar to that seen in male rats. Ovariectomy did not cause any change of paw edema except at the late stage of convalescence when compared with the sham-operated group. Ovariectomy-induced faster recovery from edema but did not affect the severity of hyperalgesia. Moreover, there was a similar amount of IRAP expression in ovariectomized and sham rats. When estradiol (E2) was given together with OT, OT-induced anti-hyperalgesia was abolished at the developmental stage of hyperalgesia in ovariectomized rats. These results show an inhibitory role of female hormones generated from ovaries (mainly estrogen) in the sex difference of anti-hyperalgesia induced by OT. This study suggests the feasibility of a novel OT-based remedy to treat hyperalgesia in men and in menopausal women no receiving hormonal supplements. Highlights: We verified the sex difference of anti-hyperalgesia induced by Oxytocin (OT). OT induced significant anti-hyperalgesia in male rats but not in female rats. OT caused a significant anti-hyperalgesia effect in ovariectomized female rats. OT-induced anti-hyperalgesia was abolished when estrogen was given together with OT. Estrogen involved in the absence of OT-induced anti-hyperalgesia in female rats.